2012
DOI: 10.1128/aac.00639-12
|View full text |Cite
|
Sign up to set email alerts
|

HIV gp120 H375 Is Unique to HIV-1 Subtype CRF01_AE and Confers Strong Resistance to the Entry Inhibitor BMS-599793, a Candidate Microbicide Drug

Abstract: b BMS-599793 is a small molecule entry inhibitor that binds to human immunodeficiency virus type 1 (HIV-1) gp120, resulting in the inhibition of CD4-dependent entry into cells. Since BMS-599793 is currently considered a candidate microbicide drug, we evaluated its efficacy against a number of primary patient HIV isolates from different subtypes and circulating recombinant forms (CRFs) and showed that activity varied between ϳ3 M and 7 M at 50% effective concentrations (EC 50 s). Interestingly, CRF01_AE HIV-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 80 publications
1
44
1
Order By: Relevance
“…It appeared that the S375Y mutation demonstrated major resistance to all NBD compounds tested, either alone or in combination with other mutations. The S375H mutation common to most subtype CRF01_AE HIV-1 viruses, which showed resistance to BMS-378806 in this study, was reported earlier to confer resistance to a candidate microbicide drug, BMS-599793, targeted to gp120 (58). The S375Y mutant and any of its combinations proved remarkably resistant to BMS-378806 (63).…”
Section: Discussionmentioning
confidence: 87%
“…It appeared that the S375Y mutation demonstrated major resistance to all NBD compounds tested, either alone or in combination with other mutations. The S375H mutation common to most subtype CRF01_AE HIV-1 viruses, which showed resistance to BMS-378806 in this study, was reported earlier to confer resistance to a candidate microbicide drug, BMS-599793, targeted to gp120 (58). The S375Y mutant and any of its combinations proved remarkably resistant to BMS-378806 (63).…”
Section: Discussionmentioning
confidence: 87%
“…CRF01_AE HIV-1 isolates have a highly conserved histidine residue at Env position 375 (Fig. 1E), which was recently shown to be important for CD4 interaction (27) but also to confer strong resistance to the BMS-599793 entry inhibitor (36). To evaluate whether His 375 influences the recognition of infected cells by ADCC-mediating antibodies and HIV ϩ sera, His 375 in the CRF01_AE 703357 strain was replaced by a serine (H375S).…”
Section: Resultsmentioning
confidence: 99%
“…6 Nonetheless, the development of broadly effective Env protein inhibitors has encountered obstacles due to structural flexibility and mutagenic permissiveness of this target and consequent potential for conformational masking and drug resistance. 79 Inhibitors that could disrupt the essential binding and conformational rearrangement program built into the Env protein trimer could represent an effective means to inactivate the virus and block cell entry.…”
Section: Introductionmentioning
confidence: 99%